ANALISIS TEORI PSIKOLOGI SERTA IMPLEMENTASINYA TERHADAP KEHIDUPAN SOSIAL REMAJA - Bahari, Lalu Pradipta Jaya (Universitas Tanjungpura, 2022)
Adolescence has many interesting things to study, especially on the concept of social psychology. It is important to note that the community itself assumes that adolescence is a time when a child begins to look for his identity. This creates a lot of positive and negative images related to teenagers. there are many socially deviant behaviors that we usually find and who do it are teenagers. Examples of such behavior are bullying, promiscuity, and drug abuse. This article aims to invite readers to think a little more scientifically related to adolescent problems. It is hoped that this article can provide benefits for readers to help teenagers around the reader to become a better person.